If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -91 = n + -42 Reorder the terms: -91 = -42 + n Solving -91 = -42 + n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. -91 + -1n = -42 + n + -1n Combine like terms: n + -1n = 0 -91 + -1n = -42 + 0 -91 + -1n = -42 Add '91' to each side of the equation. -91 + 91 + -1n = -42 + 91 Combine like terms: -91 + 91 = 0 0 + -1n = -42 + 91 -1n = -42 + 91 Combine like terms: -42 + 91 = 49 -1n = 49 Divide each side by '-1'. n = -49 Simplifying n = -49
| -6x-8=x+27 | | 2.9q-2.5-4.4q=-2.5q-4.1 | | 0.2t-3=-17 | | (x+2)(x+3)=56 | | .4x-3=21 | | 3x+8(1/2x+35) | | k=xyz | | .4-3=21 | | 1/4(x+2)=1/3x | | X+8+x=-6 | | x+23=11x+13 | | -12+[(17-18)-(8-6)]= | | y=3-0 | | 17-6x=4x+9-9x | | 3(11x-7)=13x+26 | | 38+104+x=180 | | 9r^2=-9 | | 6x-7yi-6=3i-1 | | 486=450-18g | | -14(-14)= | | -73=-x-6x-10 | | -14(-13)= | | 3+8x+4x^2=0 | | -2a+7=-11 | | x^4-6x+38= | | 9r^2+9=0 | | -14x-13= | | 36(5-4)+2(8-4)+8= | | 5.6=-11.76 | | -2a+7=-7 | | 7x+10+3x=-90 | | 9x-4=x+20 |